First example of Ugi's amine as a platform for the construction of chiral coordination polymers: synthesis and properties - Gilmanova, Leisan; Shekurov, Ruslan; Khrizanforov, Mikhail; Ivshin, Kamil; Kataeva, Olga; Bon, Volodymyr; Senkovska, Irena; Kaskel, Stefan; Vasily, Miluykov (New Journal of Chemistry, 2021)
Here, the first example of phosphinic acid containing Ugi's amine (HL) is presented. Utilization of this phosphinic acid as a ligand along with 4,4′-bipyridine (bpy) facilitated the synthesis of the first coordination polymer based on Ugi's amine with the composition Ni(bpy)2L2. The crystal structure of both ligand and polymer were solved from the single-crystal X-ray diffraction data. The acid exists as zwitterion and crystallizes as a mixture of two racemic forms. The coordination polymer comprises layers composed of Ni(bipy)2, terminated by L as monodentate ligands, coordinated to Ni through the phosphinate group. The solid-state cyclic voltammetry was used as an analytical tool, which made it possible to estimate the iron to nickel ratio in the structure of coordination polymer. The cathodic shift of the oxidation potential of the ferrocene fragment in the polymer in comparison to free acid demonstrates a strong interaction of iron and nickel within the coordination polymer structure.
CRIS-Team Scopus Importer:2022-04-14